Strategi Penangulangan Kemiskinan dan Ketahanan Pangan Melalui Kebijakan Beras Daerah (RASDA) dan Beras PNS pada Program Bela Beli Kulonprogo (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This research discusses strategies for poverty alleviation and food security through the regional rice program and civil servant rice which are derivative programs from the Bela Beli Kulon Progo program. The research method used is descriptive qualitative. the type of data used is secondary data. The results of this study, the regional rice program (RASDA) and civil servant rice can improve the welfare of food producing farmers and at the same time realize Law no. 18 of 2012 concerning Food Security which mandates to achieve affordability of food by implementing policies in the food sector. The Rasda program was implemented concurrently with rice for civil servants. This program aims to spur economic growth and improve the welfare of Kulonprogo farmers. As the main executor of the Regional Rice Program (Rasda) and Civil Servant Rice is the Association of Farmers Groups (Gapoktan) consisting of Panca Manunggal, Ngestiharjo, Makmur Sejahtera, Among Farmers, Sidomaju, Sari Mulyo, Sumber Makmur. The conclusion from this study is that regional rice and civil servant rice can support food security and contribute to poverty alleviation